A sketch of early days on the Purgatory - Taylor, Morris F. (Trinidad, CO Trinidad State Junior College, 1959)
A history of early life on the Purgatory River.
Includes Bibliography
38793
Keywords: New Mexico -- Northeastern New Mexico and Southeastern Colorado; Purgatory River -- History -- Southeastern Colorado; Purgatory River -- American history